Cognitive interference model of computer anxiety: Implications for computer-based assessment. - Smith, Brooke; Caputi, Peter (Computers in Human Behavior, 2007)
In this paper, the cognitive interference model of computer anxiety (CIM-CA) is introduced as a theoretical framework for the assessment of computer anxiety and its effect on computer-based test (CBT) performance and test equivalence. Unlike other situation-specific anxieties, research on computer anxiety has not been founded on clear theories or models. Hence, the CIM-CA is intended as a new heuristic framework for representing the dispositions and cognitive processes that predispose individuals to react with state computer anxiety over a range of situations involving computers. In particular, the model focuses on the mediating role of negative computer thoughts on the computer anxiety-performance linkage. The CIM-CA model also provides a theoretical framework for analysing the effect of computer anxiety on CBT performance. Future research opportunities pertaining to the computer anxiety-performance linkage are discussed in the context of computerised cognitive assessment. Copyright (c) 2007 Elsevier Ltd